Mercury accumulation and tissue-specific antioxidant efficiency in the wild European sea bass (Dicentrarchus labrax) with emphasis on seasonality - Mieiro, C. L.
The main goal of this study was to assess both mercury (Hg) accumulation and organs' specific oxidative stress responses of gills, liver and kidney of Dicentrarchus labrax with emphasis on seasonality. Fish were collected in cold and warm periods in three stations: reference, moderated and highly contaminated sites. Our results showed that seasonal factors slightly influenced Hg accumulation between year periods (cold and warm) and strongly affected organs' response basal levels. In contrast, seasonality seemed not to influence oxidative stress responses, since similar response patterns were obtained for both year periods, and moderate degree of antioxidant responses was obtained. Moreover, the oxidative stress profile may be attributed to Hg contamination degree, which showed organ-specific response and accumulation patterns. Hence, gills showed to be able to adapt to Hg contamination, and in opposition, kidney and liver demonstrated some vulnerability to Hg toxicity. The critical Hg concentrations indicated specific threshold limits for each organ. Overall, seasonality should be taken into account in monitoring programmes, helping to characterize the individuals' reference values of response and thus to discriminate between the effects induced by natural causes or by contamination.